Pope and Horace: imitation and independance - Ohsumi, Megumi (My University, 2013)
The present dissertation concerns Alexander Pope’s Horatian Imitations, which were modeled principally on Horace’s Satires and Epistles. It focuses on the parallels which the English poet sought to draw with the Roman poet with regards to his background as an outsider, his rise to success, and his views on the relationship between politics and poetry. The argument lies in the idea that Pope’s motivation for composing the Horatian Imitations was based on multiple factors. Taking a chronological approach, the dissertation consists of ten chapters and may be divided into three parts: Chapters 1-5 discuss the poets’ origins and path to fame, as well as explaining the cultural and historical context of eighteenth-century English literature; Chapters 6-8 focus on poetry and politics and provide comparative analyses of Horace’s poems and Pope’s corresponding Imitations; Chapters 9 and beyond, while pointing out certain similarities, trace the progression of Pope’s wavering views towards the ancient poet until he eventually renounces the Horatian series. The first chapter opens with Pope’s birth and origins. Aspects such as Catholicism and physical deformity are presented as struggles which were unique to Pope, but the chapter demonstrates how Pope in his Imitations cleverly manages to align his background with Horace’s in accentuating their ability to overcome adverse circumstances. The second chapter attempts to define imitation in Pope’s era. It also discusses parallel texts and argues that the purpose of the parallel texts in Pope’s Imitations was to enable him to assume an authority that was equal to Horace’s. The third and fourth chapters concern Pope’s ascent to becoming a renowned poet. Chapter 3 provides information on different classical authors as material for translation into English and highlights Horace as being one of the most popular. The chapter argues Pope’s ambition in attempting to surpass Dryden as both writer and translator. Chapter 4 deals with the growing book trade in eighteenth-century England and the argument centers on Pope’s persistence in choosing an independent path instead of relying on the system of patronage. The fifth chapter on patronage first points out Pope’s uniqueness in his refusal of patronage, and the rest of the chapter argues that Horace’s patron-client relationship with Maecenas differed from that with Augustus. This leads the reader to the chapters on politics. The sixth chapter contrasts Horace’s consciousness of his limits on freedom under Augustus in Sat. 2.1 to Pope’s temerity, in his Imitation, in defying censorship under King George II and Sir Robert Walpole. Chapters 7 and 8 focus on Horace’s Ep. 2.1 and Pope’s corresponding Imitation and argue that, unlike Horace’s Augustus, Pope sees no hope of proper appreciation and diffusion of the literary arts by his king. Chapter 9 presents the similarities between the two poets. It argues that Pope sees parallels with Horace, in such matters as their bachelorhood, but that Pope cannot detach the idea that Horace has become an insider in mainstream society while he remains an outsider. The final chapter focuses on Pope’s two Dialogues and posthumously published 1740, which, though not based on Horace’s poems, nevertheless serve as conclusions to the Horatian Imitations. The chapter argues that, although Pope eventually falls out with Horace, it is only so that he may turn his focus, from comparison with Antiquity, to the present and future of his nation and the welfare of his own people. The dissertation concludes with Pope’s newly adopted assumption that Horace was, unlike himself, a court poet. However, notwithstanding the apparent divergence, the reader is reminded that Pope’s admiration for the ancient poet did not change. Furthermore, it demonstrates that, although Pope expects no improvement in the current Hanoverian regime, he still remains optimistic that a better England awaits his people in the future.
Thèse de doctorat : Université de Neuchâtel, 2013
Keywords: poésie augustéenne; patronage romain; poète et politique sous Auguste; littérature anglaise du dix-huitième siècle; traduction et imitation; études de réception; littérature comparée; augustan poetry; roman patronage; poets and politics under Augustus; eighteenth-century english literature; translation and imitation; reception studies; comparative literature